Books, Culture and the European Challenges they Face - Grilc, Uroš (Javnost-The Public, 2004)
In the article that takes as its starting point two of the fundamental European Union (EU) principles regarding the issues of culture, cultural diversity and plurilingualism, the author researches the effects to date of the absence of a common European cultural policy. In two concrete cases n taxation on books and public lending rights n he shows that the absence of a common European cultural policy has resulted in practice in the inadequate implementation of these fundamental principles. Recent moves in relation to the formulation of a European constitution point to an awareness of the need for a more active European cultural policy that actually provides a framework within which member states would be independent in the formulation of their own cultural policy models.